Young children's negotiation of language policies and multilingual curriculum at an ethnic minority elementary school in rural China. Issue 2 (June 2023) - Wang, Jue
Through interpreting the status of Hoche language and cultural practices from community voices, this ethnographic case study conducted in a minority language school centers on five Han and Hoche ethnic minority children's positions toward multi-language learning. My research explores how these children negotiate the policies and multilingual curriculum that illuminates the multilayered tensions between local issues and global transformation. Findings indicate that policies situate Hoche as a romantic representation of the past, whereas the narratives I gathered from Hoche and Han children's attitudes and ideologies about language show that younger generations are oriented toward future opportunities and influenced by globalization. This work contributes to scholarship on the education of minority children during a period of rapid industrialization by extending our understanding of ethnicity, diversity, and inclusivity issues via children's perspectives. Shedding light onto the lives of Hoche and other ethnic minority children's language practices, this paper is a call to urgently address power inequities in the ideologies and pedagogies enacted in service of Indigenous reclamation.